Iatrogenic Transient Complete Heart Block in a Preexisting LBBB - Adil S. Wani; Adebayo Fasanya; Prachi Kalamkar; Christopher A. Bonnet; Omer A. Bajwa (Case Reports in Critical Care)
Catheter induced cardiac arrhythmia is a well-known complication encountered during pulmonary artery or cardiac catheterization. Injury to the cardiac conducting system often involves the right bundle branch which in a patient with preexisting left bundle branch block can lead to fatal arrhythmia including asystole. Such a complication during central venous cannulation is rare as it usually does not enter the heart. The guide wire or the cannula itself can cause such an injury during central venous cannulation. The length of the guide wire, its rigidity, and lack of set guidelines for its insertion make it theoretically more prone to cause such an injury. We report a case of LBBB that went into transient complete heart block following guide wire insertion during a central venous cannulation procedure.